2019
DOI: 10.7124/feeo.v24.1110
|View full text |Cite
|
Sign up to set email alerts
|

Lactose intolerance and its association with the exogamy degree among the population of eastern Ukraine

Abstract: Aim. The aim of our study was to evaluate the relationship between exogamy degree and lactose assimialation among the population of Eastern Ukraine in the Kharkiv region. Methods. The analysis included information on consumption and assimilation of milk and dairy products by 733 people aged from 14 to 79 years were. Statistical analysis included Shapiro-Wilk test, Pearson fitting (χ2) criterion and Spearman’s correlation analysis. Results. The lactose tolerance (LT) phenotype was found in 69.5%, whereas lactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Lactose intolerance is the risk factor for fractures and osteoporosis but is also could associated with gastrointestinal pathologies. Our results obtained previously indicate that patients with CTGA genotype had osteoporosis and disorders of the gastrointestinal tract, such as gastritis (43 %), peptic ulcer (29 %), stomach cancer (12.5 %) and others [6].…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Lactose intolerance is the risk factor for fractures and osteoporosis but is also could associated with gastrointestinal pathologies. Our results obtained previously indicate that patients with CTGA genotype had osteoporosis and disorders of the gastrointestinal tract, such as gastritis (43 %), peptic ulcer (29 %), stomach cancer (12.5 %) and others [6].…”
Section: Resultssupporting
confidence: 55%
“…The tendency for associative marriages has the effect of increasing the inbreeding level. It leads to a decrease in genetic diversity, an increase in the number of similar loci in chromosomes during conjugation, and thus to an increase in the recombination processes associated with chromosome rearrangements, and consequently to a decrease the number of homozygotes [13].The results of our previous studies have shown that people who consumed milk and dairy products in childhood and decreased this ability with age had heterozygous genotypes: CTGA of SNPs-13910C-T (rs4988235) and 22018G-A (rs182549) of MCM6gene [6]. Therefore, the results of this study are consistent with previous findings.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…According to our results, in this group the lowest value of persons with the lowest parents' exogamy degree was noted. As we have shown earlier, parameters of persons exogamy degree may affect the frequency of genetic recombination [16].…”
Section: Discussionmentioning
confidence: 57%